Corticospinal tract involvement in spinocerebellar ataxia type 3: a diffusion tensor imaging study - Inada, Bruno Shigueo Yonekura; Rezende, Thiago Junqueira Ribeiro; Pereira, Fernando Vieira; Garcia, Lucas Ávila Lessa; da Rocha, Antônio José; Neto, Pedro Braga; Barsottini, Orlando Graziani Povoas; França Jr, Marcondes Cavalcante; Pedroso, José Luiz (Neuroradiology, 2021)
Purpose The aim of this study was to evaluate the integrity of the corticospinal tracts (CST) in patients with SCA3 and age- and gender-matched healthy control subjects using diffusion tensor imaging (DTI). We also looked at the clinical correlates of such diffusivity abnormalities. Methods We assessed 2 cohorts from different Brazilian centers: cohort 1 ( n = 29) scanned in a 1.5 T magnet and cohort 2 ( n = 91) scanned in a 3.0 T magnet. We used Pearson’s coefficients to assess the correlation of CST DTI parameters and ataxia severity (expressed by SARA scores). Results Two different results were obtained. Cohort 1 showed no significant between-group differences in DTI parameters. Cohort 2 showed significant between-group differences in the FA values in the bilateral precentral gyri ( p < 0.001), bilateral superior corona radiata ( p < 0.001), bilateral posterior limb of the internal capsule ( p < 0.001), bilateral cerebral peduncle ( p < 0.001), and bilateral basis pontis ( p < 0.001). There was moderate correlation between CST diffusivity parameters and SARA scores in cohort 2 (Pearson correlation coefficient: 0.40–0.59). Conclusion DTI particularly at 3 T is able to uncover and quantify CST damage in SCA3. Moreover, CST microstructural damage may contribute with ataxia severity in the disease.